2017
DOI: 10.1111/tbed.12699
|View full text |Cite
|
Sign up to set email alerts
|

First report of the novel atypical porcine pestivirus in Spain and a retrospective study

Abstract: This study aimed to provide information regarding viral pathogenesis and molecular epidemiology linked with recently reported atypical porcine pestivirus (APPV) strains and to determine the circulation of APPV in Spain from 1997 to 2016. Two-day-old piglets with moderate-severe congenital tremor (CT) from a Spanish farm were received for diagnostic purposes. Sera, nasal and rectal swabs and tissue samples were collected. qRT-PCR was performed in these samples, and a retrospective study to detect APPV RNA was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 19 publications
3
76
1
5
Order By: Relevance
“…In one study, 1615 nt of APPV NS2‐3 region were used to calculate the nucleotide substitutions per site per year (s/s/y) among the Spanish strain 2001, Spanish strain 2015, and German strain 2015. The results show that during the past 14 years, a mutation rate of 2.65 × 10 −3 s/s/y has occurred between the Spanish strains 2001, and 2005, while it is 3.62 × 10 −3 s/s/y between the Spanish strain 2001, and the German strain 2015 . Both high‐mutation rates were comparable with that of CSFV reported previously, suggesting that the APPV may have been evolving within the range of mutation rate as pestiviruses have.…”
Section: Genetic Diversity and Evolution Of Appvsupporting
confidence: 78%
See 4 more Smart Citations
“…In one study, 1615 nt of APPV NS2‐3 region were used to calculate the nucleotide substitutions per site per year (s/s/y) among the Spanish strain 2001, Spanish strain 2015, and German strain 2015. The results show that during the past 14 years, a mutation rate of 2.65 × 10 −3 s/s/y has occurred between the Spanish strains 2001, and 2005, while it is 3.62 × 10 −3 s/s/y between the Spanish strain 2001, and the German strain 2015 . Both high‐mutation rates were comparable with that of CSFV reported previously, suggesting that the APPV may have been evolving within the range of mutation rate as pestiviruses have.…”
Section: Genetic Diversity and Evolution Of Appvsupporting
confidence: 78%
“…Currently, tissue tropism of APPV was primarily determined by qRT‐PCR. In one study from the 2‐day‐old piglets, high‐APPV RNA loads were found in the tonsil, spleen, and thymus samples, while moderate RNA loads in the sera, nasal/rectal swabs, cerebrospinal fluid, and cerebrum . In another study, the APPV can be detected in nearly all tissues with the highest‐RNA levels in the submaxillary lymph nodes, and moderate RNA levels in the peripheral lymphoid organs (spleen, tonsil, and inguinal lymph node), nervous system (brain stem, brain, and cerebellum), and digestive system (duodenum) .…”
Section: Pathogenesis and Pathologymentioning
confidence: 97%
See 3 more Smart Citations